2013
DOI: 10.1103/physrevb.87.245415
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing atomic resolution of force microscopy in ambient conditions

Abstract: Ambient operation poses a challenge to atomic force microscopy because in contrast to operation in vacuum or liquid environments, the cantilever dynamics change dramatically from oscillating in air to oscillating in a hydration layer when probing the sample. We demonstrate atomic resolution by imaging of the KBr(001) surface in ambient conditions by frequency-modulation atomic force microscopy with a cantilever based on a quartz tuning fork (qPlus sensor) and analyze both long-and short-range contributions to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
179
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(184 citation statements)
references
References 59 publications
4
179
0
Order By: Relevance
“…95,96 The stability provided by E c can be understood from the proportionality to k and A square. 97,98 The oscillation amplitude A can be arbitrarily set as a set-point in dAFM.…”
mentioning
confidence: 99%
“…95,96 The stability provided by E c can be understood from the proportionality to k and A square. 97,98 The oscillation amplitude A can be arbitrarily set as a set-point in dAFM.…”
mentioning
confidence: 99%
“…3 For example, dynamic AFM (dAFM) modes of operation are typically employed to map the topography of conductors and insulators with nanoscale, 4 molecular, 5 sub-molecular, [6][7][8][9] and sometimes atomic resolution. [10][11][12] These dynamic modes typically provide alternative channels 13 to simultaneously map compositional variations. 14 The scientific community is in fact actively seeking to increase the number 15 and sensitivity 13 of contrast channels 12,16,17 since these can be employed to quantify 18,19 nanoscale properties and enhance resolution and/or contrast.…”
mentioning
confidence: 99%
“…14 The scientific community is in fact actively seeking to increase the number 15 and sensitivity 13 of contrast channels 12,16,17 since these can be employed to quantify 18,19 nanoscale properties and enhance resolution and/or contrast. 12,20,21 Recently, two groups 8,11 have independently reported that the tip of the AFM can be made to oscillate with subnm amplitudes, and in the proximity of the surface, i.e., near or in the mechanical contact region, while enhancing resolution even in the presence of adsorbed water layers in ambient conditions. Here, we introduce bimodal AFM, where the second flexural mode of the cantilever is excited with ultra-small oscillation amplitudes while oscillating under such conditions.…”
mentioning
confidence: 99%
See 2 more Smart Citations